Transforming hospital crowd management: a case study on Pravesh electronic visitor management system - PRIYA, P S KARPAGA; G. Prabhune, Akash (BOHR International Journal of Internet of things, Artificial Intelligence and Machine Learning, 2024)
In this case study, we will delve into the development and impact of “Pravesh—An Electronic Visitor Management System,” envisioned to streamline hospital crowd management, especially in the IP and OP departments of small to large-scale hospitals in India. Dr. Kalaivani and Mr. Arun Senthilkumar (co-founders) were inspired by a personal encounter to improve patient care outcomes and reduce the manual workload of the hospital staff by streamlining the visitor and attender management. Pravesh was developed using a Low-Code/No-Code platform in combination with an Agile-based Scrum Framework. The application comprises two passes: a visitor pass which can be generated by scanning a QR code placed at the hospital registration desk, and an attender pass that will be issued to a patient’s attendee during an inpatient registration by the hospital front-desk executives. Pravesh was pilot tested at a 30-bedded hospital in Bengaluru, successfully demonstrating its effectiveness in saving staff time and improving patient safety by limiting the number of visitor footfalls at the hospital per day. The positive feedback received from the hospital crowd management. The incorporation of technology in healthcare settings has facilitated overcoming the challenges faced by healthcare professionals as well as patients. Additionally, the founders are planning to scale up Pravesh with new features to fit the specific needs of different hospitals to position itself in the current Indian healthcare ecosystem.